Studi Pengaruh Hambatan Samping Terhadap Kinerja Jalan Panglima Polem Kota Banda Aceh - Fahryza Yuza; Ichsan Syahputra; Amalia Effendy (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Jalan Panglima Polem Kota Banda Aceh, according to function is an arterial road. Based on the Banda Aceh City Regional Spatial Plan (RTRW) in 2009/2029, this area is designated as the downtown area, therefore along the road there are shops, offices and restaurants. Because of the large draws of shops and restaurants the traffic flow in the region is sometimes not smooth, this condition is exacerbated by the side constraints due to heavy shopping activities, street vendors and a very long time in and out of vehicle exchanges. Data was collected in each direction, namely A and B for three days, namely on Monday, Thursday, Saturday, the results of this study found that the highest traffic volume occurred on Monday, direction A on March 9, 2020, amounting to 1,118 pcu / hour, with mild side obstacle class, free flow speed is 56 km / hour, road capacity is 1571 pcu / hour, saturation degree is 0.71, and traffic speed is 33.33 km / hour, and the highest traffic volume direction B occurs at Monday, March 9, 2020 is 805 pcu / hour, with very mild side barriers, free flow acceleration is 57 km / hour, road capacity is 1603 pcu / hour, saturation degree is 0.50, and traffic speed is 31.64 km /hour.